Added sugars: consumption and associated factors among adults and the elderly. São Paulo, Brazil Açúcares de adição: consumo e fatores associados entre adultos e idosos. São Paulo, Brasil - Milena Baptista Bueno; Dirce Maria Lobo Marchioni; Chester Luis Galvão César; Regina Mara Fisberg (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2012)
OBJECTIVE: To investigate added sugar intake, main dietary sources and factors associated with excessive intake of added sugar. METHODS: A population-based household survey was carried out in São Paulo, the largest city in Brazil. Cluster sampling was performed and the study sample comprised 689 adults and 622 elderly individuals. Dietary intake was estimated based on a 24-hour food recall. Usual nutrient intake was estimated by correcting for the within-person variance of intake using the Iowa State University (ISU) method. Linear regression analysis was conducted to identify factors associated with added sugar intake. RESULTS: Average of energy intake (EI) from added sugars was 9.1% (95% CI: 8.9%; 9.4%) among adults and 8.4% (95% CI: 8.2%; 8.7%) among the elderly (p < 0.05). Average added sugar intake (% EI) was higher among women than among men (p < 0.05). Soft drink was the main source of added sugar among adults, while table sugar was the main source of added sugar among the elderly. Added sugar intake increased with age among adults. Moreover, higher socioeconomic level was associated with added sugar intake in the same group. CONCLUSIONS: Added sugar intake is higher among younger adults of higher socioeconomic level. Soft drink and table sugar accounted for more than 50% of the sugar consumed. OBJETIVO: Avaliar o consumo alimentar, principais fontes dietéticas e fatores associados à ingestão acima da recomendação de açúcares de adição. MÉTODOS: Um inquérito populacional domiciliar foi realizado em São Paulo, a maior cidade do Brasil. A população de estudo foi obtida por um processo de amostragem por conglomerados e composta por 689 adultos e 622 idosos. O consumo alimentar foi estimado por um recordatório de 24 horas. Os valores nutricionais foram ajustados pela variância intra pessoal, utilizando o método instituído pela Universidade de Iowa (ISU). A regressão linear foi conduzida para identificar os fatores associados ao consumo de açúcares de adição s. RESULTADOS: A média de energia proveniente dos açúcares de adição foi de 9,1% (IC 95%: 8,9%; 9,4%) entre adultos e 8,4% (IC 95%: 8,2%; 8,7%) entre idosos (p < 0,05). A média do consumo de açúcares de adição foi maior entre mulheres quando comparada à dos homens (p < 0,05). A principal fonte de açúcares de adição foi refrigerante entre adultos, enquanto que entre idosos foi açúcar de mesa. O consumo de açúcares de adição aumentou conforme a idade entre adultos. Além disso, o alto nível socioeconomico esteve associado com o consumo de açúcares de adição entre adultos. CONCLUSÕES: O consumo de açúcares de adição é maior entre adultos de nível socioeconômico alto. Refrigerantes e açúcares de mesa são responsáveis por mais de 50% do consumo de açúcares.